Investigation of PESTEL factors driving change in capital project organizations - Bou Hatoum, Makram; Nassereddine, Hala; Musick, Sean; El-Jazzar, Mahmoud (Frontiers in Built Environment, 2023)
In a volatile, uncertain, complex, and ambiguous environment, organizational change has been a central concern for capital project organizations, that continue to suffer from poor project performance in a growing industry. As such, capital project organizations must understand the changing environment and the factors driving change within their organizations to remain successful in a changing environment and adapt to change. To help the capital projects industry achieve successful organizational change efforts, this paper aims to 1) identify the external factors that are pushing capital project organizations to change and 2) investigate whether these factors impact organizations differently. To achieve the desired objective, a total of 22 PESTEL (political, economic, social, technological, environmental, and legal) factors were identified and validated with a group of 14 subject matter experts and defined via the context of literature. Then, the factors were evaluated via an online survey to understand whether they impact organizations differently based on their age maturity (including contemporary, transitional, and legacy organizations) and type of work (including owners, contractors, and service providers). Findings from this study can provide capital project practitioners and researchers with valuable insights needed to understand the external factors shaping change within the industry.